2021
DOI: 10.1002/hlca.202100015
|View full text |Cite
|
Sign up to set email alerts
|

Design of Chiral NHC‐Carboxylates as Potential Ligands for Pd‐Catalyzed Enantioselective C−H Activation

Abstract: Despite numerous efforts, the synthesis of scalemic carbo-and heterocycles through Pd 0-catalyzed C(sp 3)À H activation employing chiral ancillary ligands or chiral bases is still limited. Inspired by the recently reported outstanding performance of IBiox-type NHC ligands and bifunctional ligands in similar transformations, a new class of bifunctional NHC-ligands bearing a pendant carboxylate group was designed. A library of 10 imidazolium-carboxylic acids was obtained in five to six steps from enantiopure L-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…First, the 2-acetylfuran was coupled with several aryl bromides in the presence of the Pd-PEPPSI complexes (3a-e). Complete conversion was obtained when 4-bromobenzaldehyde and 4-bromoacetophenone were used, with 73-95% yields (Table 3, entries [28][29][30][31][32][33][34][35][36][37][38][39][40][42][43][44][45]. Good conversions were obtained with the rest of the aryl bromides using all the complexes except the reaction with 4-bromotoluene in the presence of 3a catalyst, which showed 79% conversion (Table 3, entry 1).…”
Section: Optimization Of the Reaction Conditions For The C-h Bond Fun...mentioning
confidence: 99%
See 1 more Smart Citation
“…First, the 2-acetylfuran was coupled with several aryl bromides in the presence of the Pd-PEPPSI complexes (3a-e). Complete conversion was obtained when 4-bromobenzaldehyde and 4-bromoacetophenone were used, with 73-95% yields (Table 3, entries [28][29][30][31][32][33][34][35][36][37][38][39][40][42][43][44][45]. Good conversions were obtained with the rest of the aryl bromides using all the complexes except the reaction with 4-bromotoluene in the presence of 3a catalyst, which showed 79% conversion (Table 3, entry 1).…”
Section: Optimization Of the Reaction Conditions For The C-h Bond Fun...mentioning
confidence: 99%
“…These catalysts work as oxidants. Plentiful N-heterocyclic carbene catalysts based on various metal complexes, such as Pd, 27,28 Pt, 29 Rh, 30 Ir, 31 Ru, 32 Co, 33 Fe, 34 Ni, 35 Cu, 36 Ag, 37 and Au, 38 have been used for the C–H bond functionalization reaction. Although palladium NHC complexes have strong electron donor and flexible steric bulkiness properties compared to phosphine and N-donor ligands, they also have hydrolytic instability, due to which their application in cross-coupling reactions has not been prominent.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42][43][44] Additionally, the structure of monocarboxylate anions was shown to improve the reactivity in certain cases, [45][46][47][48][49] while the use of chiral phosphates was demonstrated in enantioselective transformations. [50][51][52][53][54] The impact of the tethering of carboxylate and phosphine donors, which can restrict the orientation of the anion, on enantioselectivity in intramolecular CÀ H arylation reactions was demonstrated by the Baudoin group (Figure 1c), [55][56][57][58] while the Yu group showed that ligands containing a neutral N-donor and a deprotonated amide anion enable enantioselective functionalization of the β-C(sp 3 )À H bonds of amides. [42,59] Furthermore, the design of rigid backbones that offer precise control over anion coordination geometry can be an enabling factor for catalytic reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers have focused on this interesting field of palladacycles and intensively explored their potential applications [12,30]. Today, many examples of palladacycles exist that show high catalytic activity in Suzuki-Miyaura [31][32][33][34][35][36][37][38][39][40][41][42], Sonogashira [41][42][43], Heck [44][45][46], Buchwald-Hartwig [47][48][49][50] coupling reactions, and carbonylation reactions [51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%